TINGKAT KERENTANAN BENCANA KEKERINGAN KAWASAN PERTANIAN PANGAN DI KECAMATAN PALAS, KABUPATEN LAMPUNG SELATAN - Luqeeto Lazuardi Nur; Zulqadri Ansar (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
The phenomenon of ENSO (El-Nino Southern Oscillation) caused by climate change is closely related to the causes of drought in Indonesia as seen from historical data (BAKORNAS PB, 2007). The agricultural sector, especially food crops, is highly dependent on climatic conditions because food crops are generally seasonal crops related to excess or lack of water. Palas sub-district is the sub-district with the largest land cover of rice fields in South Lampung Regency. The type of rice field in Palas District is a rainfed rice field that is not supported by an irrigation network which will cause the area to be more susceptible to drought. This study aims to assess the level of vulnerability to drought in food agriculture areas in Palas District. This research uses a study approach, namely weighting, scoring, and reclassing the four dimensions that make up the drought vulnerability index, namely social, economic, physical, and environmental. Based on the results of the analysis of the index of vulnerability to drought, high grades are found in the villages of Bumi Daya, Bali Agung, and Mekar Mulya. The high class is driven by high social vulnerability factors such as population, age group ratios, poverty ratios, and the ratio of the last education of the population. High economic vulnerability factors such as agricultural area and livelihood ratios. High physical vulnerability factors such as water sources and irrigation infrastructure so that the area is in an area prone to drought.